The Potential of CRISPR (Clustered Regularly Interspaced Short Palindromic Repeats), Gene Editing Technology, in the Treatment of Coronary Artery Disease: A Systematic Literature Review - Mayasari, Hilda; Winda Nestamer (Open Access Indonesian Journal of Medical Reviews, 2023)
The treatment of CAD depends on the severity of the disease and the individual's risk factors. There are a number of medications that can help to slow the progression of CAD and reduce the risk of complications. The treatments for CAD can have side effects, which can make it difficult for people to adhere to their treatment plan. The treatments for CAD can be expensive, which can make it difficult for people to afford them. This is especially true for people who do not have insurance. This study aimed to conduct a systematic review to explore the potential of CRISPR in CAD management. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the potential of CRISPR in the treatment of coronary artery disease. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. CRISPR has great potential as a future therapeutic modality for coronary artery disease, where this technology is able to control various CAD risk factors and can trigger the formation of new blood vessels to overcome coronary artery blockade. However, this very potential technology still requires ethical concern studies in order to be able to maintain human sustainability.